The legislative process at the service of quality law - Bergougnous, Georges (Journal of the Belarusian State University. Law, 2020)
The article examines certain aspects of the legislative process related to the quality of the law. Attention is drawn to the requirements of clarity and openness of the parliamentary discussion during the consideration of draft laws. The requirements relating to the text of the bill are clarity, intelligibility, accessibility. The study is based on the analysis of the 1958 French Constitution and the practice of the French Constitutional Council.
Keywords: legislative process; quality of law; clarity of law; intelligibility of law; accessibility of law; France